A META-ANALYSIS ON THE EFFECTS OF PROBLEM-BASED LEARNING IN ACCOUNTING LEARNING - Novitasari Novitasari; Nurika Restuningdiah; Helianti Utami (International Journal of Economy, Education and Entrepreneurship, 2022)
This research focuses on the effect of Problem-Based Learning in accounting learning for students of SMK (Vocational High School), SMA (Senior High School), and University. In addition, this research also aims to analyze the magnitude of the effect and correlation of Problem-Based Learning on accounting learning based on education, the type of research, and the dependent variable. This research analyzed 24 research articles based on the magnitude of effect. There was 1 article with a small impact, nine articles with a medium result, and 14 articles with a significant impact